First teachers in Myron Korduba`s formation as a geographer - Valerii Rudenko; Catherine Grek (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2020)
The purpose of the publication – to discover the role of the first teachers of Professor Myron Korduba (1876 - 1947) in his formation as a geographer-scientist, teacher-innovator, on the basis of the study of little-known archival and literary sources. The study is about the contribution of Myron Korduba’s first thirteen teachers, who through their scientific and pedagogical activity during the years 1885 – 1905 influenced his formation of geographical views and worldview. It is found out that the vast majority of his mentors were classical geographers by profession after graduation from leading European universities. The scientific and pedagogical levels of Myron Korduba’s teachers, the versatility of their geographical approaches and research findings were noted.